SÍNTESE, CARACTERIZAÇÃO E ESTUDO DAS ATIVIDADES BACTERICIDAS DO COMPOSTO 2-HIDRÓXI-1,4-NAFTOQUINONATO DE PRATA(I) - Faganello, Natali; Dantas, Jaqueline; Dos Anjos, Ademir; Cabeza, Natalia; Favero, Vanessa; Facco, Janaína (ANAIS DO ENIC, 2018)
-